Will Beauty Save the Brain? Exploring the Relationship Between Eudaimonic Reels Exposure and Egyptian Gen Z's Mind and Motivations - Zaky, Petra (AUC Knowledge Fountain, 2026)
Social media entertaining content includes a mixed bag of the meaningful and the trivial. For Generation Z, whose favorite daily entertainment is shallow yet funny short-form videos (reels), there is often an invisible price paid. The loss of ability to watch long meaningful videos, distractedness from self, “Brain Rot”, glamorizing of hedonism are among the maladies left behind the attractive rabbit hole of their daily media diet. This study explores the relationship between exposure to meaningful reels, in contrast to pleasurable reels, and Gen Z’s reflective thinking, “Brain Rot” symptoms, motivation to watch long meaningful videos and life motivations between the meaningful and pleasurable. The paper aims to examine the potential of eudaimonic reels to help a generation connect with deep reflective thinking and motivate them to seek what is purposeful in life and in media. To achieve its objectives, exposure to eudaimonic and hedonic reels was analyzed for their relationship on the mind and motivations of Gen Z (ages 18–29) through an online survey with 418 responses (N = 418). Using the theory of mediated Eudaimonia and Dostoevsky’s “Beauty will Save the World” as theoretical frameworks, the findings revealed that greater exposure to eudaimonic reels led to an increased reflective thinking among Gen Z and inspired their appetite to seek to watch long eudaimonic videos. This suggests that the "snackable" allure of meaningful reels sparks a hunger for the "feast" of long-form deep audiovisual content. Additionally, the survey also found that Gen Z’s inclination towards meaningful life goals was relatively high (M = 4.21, SD = .84), despite them having a high exposure to  hedonic reels (M = 3.64, SD = 1.03). However, high exposure to both reel types is connected to high 'brain rot' features, suggesting that the quick format and nature of successive scrolling have the final word regardless of the depth or triviality of content consumed. This study aimed to show a correlation between the variables but to explain a causation is beyond its scope.